Ultra-Wide Swath SAR Imaging With Continuous PRF Variation - Gebert, Nicolas; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2010)
Innovative multi-channel synthetic aperture radar (SAR) concepts enable high-resolution wide-swath imaging, but the antenna length typically restricts the achievable swath width. This limitation can be overcome by a novel technique which is based on a single azimuth channel but operates the system with a continuously varied pulse repetition frequency (PRF) by this allowing in principle for arbitrary wide swaths. This paper introduces the basic principles and discusses design constraints for such a PRF variation. Further, a systematic performance analysis of an L-band reflector antenna system is carried out with focus on the sensitivity versus different input parameters.
DLR Import::2019-04-03